2018
DOI: 10.7554/elife.39196
|View full text |Cite
|
Sign up to set email alerts
|

Multiple neurons encode CrebB dependent appetitive long-term memory in the mushroom body circuit

Abstract: Lasting changes in gene expression are critical for the formation of long-term memories (LTMs), depending on the conserved CrebB transcriptional activator. While requirement of distinct neurons in defined circuits for different learning and memory phases have been studied in detail, only little is known regarding the gene regulatory changes that occur within these neurons. We here use the fruit fly as powerful model system to study the neural circuits of CrebB-dependent appetitive olfactory LTM. We edited the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 56 publications
(96 reference statements)
3
28
0
Order By: Relevance
“…A further member of this superfamily, CREB, is involved in wide-ranging processes including glucose homeostasis, growth-factor-dependent cell survival, nervous system development, learning, memory, synaptic plasticity, and drug adaptive responses (16). In insects, CREB has also been shown to play a role in diverse processes including long-term memory formation, waking and rest homeostasis, starvation resistance, age-dependent labor division, and environmentinduced behavioral plasticity (17)(18)(19)(20)(21). However, the role of CREB in regulating detoxification enzymes in the context of insect resistance to insecticides has never been explored.…”
Section: Significancementioning
confidence: 99%
“…A further member of this superfamily, CREB, is involved in wide-ranging processes including glucose homeostasis, growth-factor-dependent cell survival, nervous system development, learning, memory, synaptic plasticity, and drug adaptive responses (16). In insects, CREB has also been shown to play a role in diverse processes including long-term memory formation, waking and rest homeostasis, starvation resistance, age-dependent labor division, and environmentinduced behavioral plasticity (17)(18)(19)(20)(21). However, the role of CREB in regulating detoxification enzymes in the context of insect resistance to insecticides has never been explored.…”
Section: Significancementioning
confidence: 99%
“…The insect mushroom-bodies (MBs) are not only known as a center for olfactory learning and memory (Dolan et al, 2018;Felsenberg et al, 2018;König et al, 2019;Lyutova et al, 2019;Thum and Gerber, 2019;Turrel et al, 2018;e.g., Warth Pérez Arias et al, 2020;Widmer et al, 2018), they are also involved in the temporal and spatial control of locomotor activity (Besson and Martin, 2005;Helfrich-Förster et al, 2002;Lark et al, 2017;Lebreton and Martin, 2009;Mabuchi et al, 2016;Manjila et al, 2019;e.g., Martin et al, 1998;Serway et al, 2009;Sun et al, 2018;Xiong et al, 2010). In addition, (Castells-Nobau et al, 2019) (Fig.…”
Section: Foxp-ib Expression In the Drosophila Brainmentioning
confidence: 99%
“…Because only a few engram cells encode a memory, studying only a small population of cells will be beneficial for understanding the memory consolidation process. Recently, a conditional knockout line for CREB was established in the fly . To this end, the coding sequence of CREB was flanked by flippase recognition target (FRT) sites.…”
Section: Main Textmentioning
confidence: 99%
“…It was also shown that only a subset of MB neurons is required for LTM. Furthermore, the downstream neurons of these cells require CREB for LTM . Thus, this fly‐line allows the study of memory‐relevant cells in greater detail.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation